CYTOTOXIC AND ANTITUMOUR ACTIVITY OF METHANOLIC EXTRACTS OF MEDICINALLY IMPORTANT PLANTS. - K S TULSI NAIK,; KIRAGANDUR MANJUNATH,; SIDDAMADAPPA CHANDRASHEKARAN,; APPANNA V KOPPAD, (International Journal of Pharma and Bio Sciences, 2014)
Traditional knowledge reveals that most of the plants are medicinally important, especially against cancer and tumors. In the present study, plants resistant and susceptible to crown gall were analysed at laboratory level for cytotoxic and antitumor activity to know whether the plants resistant to crown gall has any constituents or compounds that are cytotoxic or anti-tumour against human tumours. Methanolic extract of Simaruba glauca(crown gall susceptible) showed highest cytotoxic activity against brine shrimps at an LC50 of 166.4ppm followed by Erythroxylum monogynum and Alianthus excelsa(crown gall resistant) extracts at LC50 of 172.3ppm and 238.3ppm respectively. We further assessed antitumor activity against the tumors induced by Agrobacterium tumefaciens using carrot disc anti-tumour bioassay. Results indicated that the extract of Simaruba glauca inhibited tumor induction on carrot discs at a lowest concentration of 100ug/ml as compared to the other two plant extract which inhibited the tumour at a concentration of 800ug/ml and above. The overall results indicate a strong cytotoxic and anti-tumour activity in a crown gall susceptible plant, while crown gall resistant plants are comparatively less cytotoxic as well as anti-tumour activity.